The Falangist project of a «sports state». From totalitarian ideology to Olympism through the images of NO-DO (1943-1961) - Cercos Raichs, Raquel; Garcia Farrero, Jordi; Vilanou Torrano, Conrad (Historia y Memoria de la Educación, 2022)
This article analyzes the ideological origins of Francoism from the perspective of a “sports state”, in the sense that physical culture, not only physical education but also sport, was seen as a way of preparing youth for the post-war peacetime after the Civil War (1936-1939). Starting from a conception of life as a sort of militia, we explore the ideological assumptions and legal provisions that laid the foundations of this “sports state”, which was dependent on the Falange. Beginning in 1943 this concept found a powerful resonance box in the images of NO-DO, coinciding with the celebration of the first National Congress of Physical Education (October 1943) that designed an action program that was not legally materialized until 1961 with the approval of the Physical Education Law. Although initially this sports nationalism, inspired by classical models (Spartan, French revolutionary), based itself on the example of European totalitarianism - especially in the organization of the Berlin Olympics (1936) by the Nazis - with the passing of time this ideological element ceded prominence to an ideology inspired by the sports pedagogy of Pierre de Coubertin. In this same direction, Olympic participation, the organization of the II Mediterranean Games (Barcelona, 1955) and the Olympic Games in Rome (1960), all with the approval of the Catholic Church, led to the consolidation of a “sports state”, which, always under the control of the Falange, assumed the values of Olympism